Aspergillosis concurrent with secondary bacterial infection in broiler chicks: a case report - Abdul Hamid, Fathin Faahimaah; Reduan, Mohd Farhan Hanif; Jasni, Sabri; Lim, Eric Teik Chung; Nordin, Muhammad Luqman; Abdullah Jesse, Faez Firdaus; Mohd Rajdi, Nur Zul Izzati; Kamaruzaman, Intan Noor Aina; Shaharulnizim, Nurshahirah (Springer, 2021)
Aspergillosis is an infectious mycotic disease which mainly affects chicks at 1 to 3 weeks of age. This report describes an outbreak of aspergillosis in 13-day-old broiler chicks reared in an open-sided poultry house on deep litter system. The total number of birds kept in the affected house was 4000 with the mortality rate of 5%. The farmer noticed signs of weakness since the arrival of day-old chicks, and eventually, 200 chicks died within 13 days. Clinical signs observed were stunted growth, dyspnoea, torticollis, incoordination, swollen hock joint, and crooked toes. Postmortem findings revealed yellow to white caseous nodular lesion at the air sacs and lung with granular appearance upon cross section. The feed and organs samples were collected for microbiological and histopathological evaluation. Aspergillus spp. were isolated on Sabouraud dextrose agar (SDA) with whitish to grey-green appearance and stained using lactophenol cotton blue. Periodic acid-Schiff (PAS) staining in the brain tissue revealed the presence of fungal hyphae and vesicle. Histopathological findings revealed alveolar emphysema, atelectasis, thrombosis, and pneumonic lung with granulomatous tissue and granulomatous encephalitis. Culling of the affected birds and removal of the contaminated bedding and feed in the house are essential measures to control and prevent the disease occurrence. Treatment using fungicide such as copper sulphate is recommended to prevent further spread of the disease in the flock.